The Use of Wordwall Interactive Media as a Learning Innovation to Foster Learning Motivation and Discipline in Pancasila Education Subjects for Third Grade Students at SD Muhammadiyah 4 Kandang Sapi Jebres - Ida Ayu Nurcahyanti; Arief Cahyo Utomo (FKIP - Universitas Riau, 2026)
This study aims to describe the use of interactive media wordwall in improving learning motivation and discipline among third-grade students at SD Muhammadiyah 4 Kandang Sapi Jebres in Pancasila Education lessons. The study uses a descriptive qualitative approach with a case study design. Data were collected through interviews, observations, and documentation of teachers and students during the learning process. The results showed that the use of Wordwall was able to increase student learning motivation because learning became more interactive, interesting, and enjoyable. Students appeared more enthusiastic, focused, and active in participating in learning activities. The time and score features on Wordwall encouraged students to complete tasks better and fostered motivation to achieve. In addition, students' discipline also improved through compliance with game rules, time management, and responsibility in completing tasks. Although there were obstacles such as time constraints, network disruptions, and differences in students' digital abilities, teachers overcame them by adjusting the media, providing assistance, and preparing devices before learning. Thus, Wordwall can be an effective innovative learning medium to increase learning motivation and discipline among elementary school students.